ASEAN-Problems and Chances of regional cooperation in East Asia - Loewen, Howard (Journal of Current Southeast Asian Affairs, 2007)

ASEAN security multilateralism and the South China Sea - Loewen, Howard (The South China Sea Conflict after the Arbitration of July 12, 2016, 2020)
Since China and the Association of Southeast Asian Nations (ASEAN) members states have agreed on a Code of Conduct draft in June 2018 commentators have stated that ASEAN security multilateralism with regard to the South China Sea will finally be equipped with binding elements and thus more effective in solving cooperation problems. Against this background this paper disagrees and argues that different factors can explain the unsatisfactory balance of ASEAN security cooperation: Great Power politics, a culture of non-binding cooperation in ASEAN, the dominance of national interests and a tendency of ASEAN-states to hedge vis-à-vis great power competition.
CRIS-Team Scopus Importer:2020-10-09

ASEM's enlargement : state-to-state or region-to-region dialogue? - Loewen, Howard (The Asia-Europe Meeting: engagement, enlargement and expectations, 2010)

Auf dem Weg zu einem asiatischen Währungsfonds - Loewen, Howard; Günther, Hilpert Hanns (SWP- Aktuell, 2010)

Das politische System der Philippinen. Eine Einführung - Loewen, Howard (Springer VS, 2017)

Democracy and Human Rights in the European-Asian Dialogue: A Clash of Cooperation Cultures? - Loewen, Howard (2008)

Demokratie und Menschenrechte im Europa-Asien Dialog - Zusammenprall von Kooperationskulturen - Loewen, Howard (Asien : the German journal on contemporary Asia, 2005)

Die ASEAN als institutionelles Zentrum regionaler Kooperation in Ostasien? - Loewen, Howard (Regionale politische und wirtschaftliche Kooperation in Asien, 2006)

Die Wahlen in den Philippinen - Loewen, Howard (Journal of Current Southeast Asian Affairs, 2007)

East Asia and Europe - Loewen, Howard (Asia Europe Journal, 2007)

East Asia's Security Architecture and the Role of the United States - Fröhlich, Stefan; Loewen, Howard (VS Verlag, 2017)

Einfache Regeln, komplexe Dynamiken: Zur Modellierung von Akteursnetzwerken in den internationalen Beziehungen, Institut für Informatik - Loewen, Howard; Köhler-Bußmeier, Michael (Berichte des Instituts für Informatik, 2010)

Foreign relations between the Philippines and the United States - Loewen, Howard (Routledge Handbook of the Contemporary Philippines, 2018)
CRIS-Team WoS Importer:2019-06-07

Indonesien als Partner deutscher Außenpolitik - Loewen, Howard; Hilpert, Hanns Günther (SWP-Studie, 2012)

Indonesien und die EU: Mehr Handel als Handeln - Loewen, Howard; Spandler, Kilian (Die EU im Beziehungsgefüge großer Staaten. komplex - kooperativ - krisenhaft, 2013)

Initiatives of Regional Integration in Asia: An Introduction - Loewen, Howard (Initiatives of Regional Integration in Asia in Comparative Perspective, 2017)

Initiatives of Regional Integration in Asia in Comparative Perspective - Loewen, Howard; Zorob, Anja (Springer, 2017)

Institutional Interplay between the Chiang Mai Initiative and the International Monetary Fund - Loewen, Howard (European Journal of East Asian Studies, 2014)

Issues of Democratic Consolidation in Romania - Loewen, Howard; Miscoiu, Sergiu (Efes, 2004)

Japans offener Bilateralismus am Beispiel der Beziehungen zur Europäischen und zur ASEAN - Loewen, Howard (Politik in Japan. System, Reformprozesse und Außenpolitik im internationalen Vergleich, 2006)

Japan und die EU - Loewen, Howard; Kevenhörster, Paul (Die Europäische Union im 21. Jahrhundert, 2007)

Neue Modelle regionaler Gemeinschaftsbildung in Ostasien - Machtbalance und Pragmatismus - Loewen, Howard (SWP- Aktuell, 2009)

Obamas Asienreise »Rückkehr« der USA als pazifische Macht? - Loewen, Howard; Tidten, Markus; Gudrun, Wacker (SWP- Aktuell, 2010)

Ostasien und Europa – Partner einer internationalen Ordnungspolitik? - Loewen, Howard (2006)

Regionale Kooperation gegen den Terrorismus in Ostasien - Loewen, Howard (Regionale politische und wirtschaftliche Kooperation in Asien, 2006)

Security Regimes in Southeast Asia – Confidence Building and the Global Nexus - Loewen, Howard (Maritime Security and Piracy. Common Challenges and Responses from Europe and Asia, 2014)

Stabilitätsdefizite der philippinischen Demokratie unter Arroyo - Loewen, Howard (Asien : the German journal on contemporary Asia, 2007)

Straße von Malakka - Loewen, Howard; Bodenmüller, Anja (Piraterie und maritime Sicherheit. Fallstudien zu Afrika, Südostasien und Lateinamerika sowie Beiträge zu politischen, militärischen, rechtlichen und ökonomischen Aspekten, 2010)

The Asia-Europe Meeting and its contribution to the political management of economic globalization - Loewen, Howard; Nabers, Dirk (Asian-European Relations. Buildings Blocks for Global Governance?, 2008)

The IMF and Regional Financial Cooperation in East Asia - Loewen, Howard (Initiatives of Regional Integration in Asia in Comparative Perspective, 2017)

Theorie und Empirie transregionaler Kooperation am Beispiel des Asia-Europe Meeting (ASEM) - Loewen, Howard (Dr. Kovač, 2003)

The quadrilateral initiative – on the way to a new security architecture in Asia? - Loewen, Howard (Journal of Current Southeast Asian Affairs, 2008)

Trade Bilateralism between Latin America and East Asia - Notions on the interplay with the WTO - Loewen, Howard (Asia and Latin America : political, economic, and multilateral relations, 2010)

Wahlen auf den Philippinen: Viel Kontinuität, etwas Wandel und eine geschwächte Präsidentin - Loewen, Howard (2007)

WTO Compatibility and Rules of Origin - Assessing Bilateral Trade Agreements between Latin American and East Asia - Loewen, Howard (Journal of Current Southeast Asian Affairs, 2009)

Zwischen Reform und Bedeutungsverlust – Der IWF nach der Jahrestagung in Singapur - Loewen, Howard (2006)